1997
DOI: 10.1111/j.1460-2695.1997.tb00396.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dynamic Strain‐ageing in the Environment Assisted Cracking Observed in Pressure Vessel Steels

Abstract: The dynamic strain ageing (DSA) behaviour of A533B Class 1 reactor pressure vessel (RPV) steel, containing 5ppm of free nitrogen, has been investigated over a wide range of strain rates from 3 x lo-' to 3-10-3 s-l and temperatures from 20 to 350°C. The DSA was observed within certain temperature ranges at all strain rates tested and its hardening effect in terms of the maximum strengthening stress (up) decreased linearly with the increase of log strain rate. The temperature to stimulate DSA was observed to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 14 publications
(14 reference statements)
1
7
0
Order By: Relevance
“…The serrations are affected by strain rate (Figure 3) and the size of the maximum load drop due to serrations decreases as the strain rate increases over the range tested. A test at a strain rate of 2.3 × 10 −5 s −1 and a temperature of 75 • C produced no serrations which agrees with previous work [16][17][18] and indicates that serrations occur at a matching combination of strain rate and temperature for a low carbon steel. The strain rate for the onset of serrations at 75 • C is approximately 1 × 10 −5 s −1 .…”
Section: Resultssupporting
confidence: 89%
“…The serrations are affected by strain rate (Figure 3) and the size of the maximum load drop due to serrations decreases as the strain rate increases over the range tested. A test at a strain rate of 2.3 × 10 −5 s −1 and a temperature of 75 • C produced no serrations which agrees with previous work [16][17][18] and indicates that serrations occur at a matching combination of strain rate and temperature for a low carbon steel. The strain rate for the onset of serrations at 75 • C is approximately 1 × 10 −5 s −1 .…”
Section: Resultssupporting
confidence: 89%
“…2, all the tensile curves show the trend of dynamic strain aging(DSG) and get more notable with temperature up. Theories of KATAD [20] and ASKINSON [21] , et al, suggested that DSG will promote environmentally assisted cracking(EAC), which causes the markedly reduced of metal material. The tensile strength of samples decrease with the increase of temperature and decrease more at 10 MPa than that at 16 MPa.…”
Section: Ssrt Resultsmentioning
confidence: 98%
“…Time‐dependent effects of environment include the phenomenon of dynamic strain ageing, 5 dynamic embrittlement, 6 hydrogen embrittlement 7 and nitrogen embrittlement 8 . According to diffusion theory, the mere presence of a gaseous environment around a solid promotes diffusion of the former into the latter.…”
Section: Environment Sensitivity Of Crack‐tip Surfacementioning
confidence: 99%
“…Intergranular diffusivity is much greater than transgranular diffusivity and is in fact referred to as ‘short‐circuit’ diffusion 9 . Most work on the subject considers the diffusion process to be time‐dependent, intergranular and as encompassing material depth of the order of at least a few grains 5–8 . Transgranular diffusion has also been studied, but under conditions that differ considerably from those associated with fatigue 10,11 .…”
Section: Environment Sensitivity Of Crack‐tip Surfacementioning
confidence: 99%
See 1 more Smart Citation